2017
DOI: 10.1080/07420528.2017.1417314
|View full text |Cite
|
Sign up to set email alerts
|

How have our clocks evolved? Adaptive and demographic history of the out-of-African dispersal told by polymorphic loci in circadian genes

Abstract: The mechanism of the molecular circadian clocks is currently understood as a transcription/translation feedback loop involving more than ten genes. Genetic variation at some of loci in these genes has been shaped by adaptation to environmental factors. In particular, latitudinal clines in allele frequency were documented in several animal species, but the contradictory conclusions were drawn from the results of rare human studies. Here we tested whether the out-of-African dispersal of human populations to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Genetics, age, gender, and environmental stimuli influence the expression of chronotype [ 7 , 9 , 10 , 12 , 17 ]. Specifically for genetics, researchers indicate from ten to 36 genes that may be involved in human chronobiology [ 24 , 25 ]. How all these variables interact to produce seven different human chronotypes is difficult to say.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetics, age, gender, and environmental stimuli influence the expression of chronotype [ 7 , 9 , 10 , 12 , 17 ]. Specifically for genetics, researchers indicate from ten to 36 genes that may be involved in human chronobiology [ 24 , 25 ]. How all these variables interact to produce seven different human chronotypes is difficult to say.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Putilov et al. investigated 1665 polymorphisms in 36 chronobiology-related genes and found out that such evolutionary changes are actually took place as a part of general adaptation [ 34 ]. We doubt that various peculiarities of human sleep habits should be called disorders.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation may be the presence of different alleles of their circadian genes, which acted to adapt the organism to different living conditions such as different latitudes. [ 80 ]. Finally, we may hypothesize that if people residing in “darkest countries” have artificial light kept on also during the daytime, they may not be as strongly influenced by higher levels of LAN because of different environment-adaptive alleles which acted to adapt the organism to light regimes diverse from the natural ones, as has been shown in animals [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans found a correlation between latitude and chronotype (morningness vs. eveningness) variation ( Leocadio-Miguel et al 2017 ; Randler and Rahafar 2017 ; Lowden et al 2018 ) and a latitudinal cline in some circadian allele frequencies ( Dorokhov et al 2018 ; Putilov et al 2018 , 2019 ), highlighting the contribution of the environment to behavior and circadian biology. Many human health effects are linked to the misalignment of chronotype ( Knutson and von Schantz 2018 ), including cancer, obesity ( Gyarmati et al 2016 ; Papantoniou et al 2016 , 2017 ; Gan et al 2018 ; Shi et al 2020 ; Yousef et al 2020 ), and diabetes ( Gan et al 2015 ; Larcher et al 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 87%